Making a Mathematical Model of Assembled Mill with Inserted Knives with Diffusion Fastening of Hard-Alloy Plates - Dubrovets Lyudmila Vladimirovna; Isamov Raim Nasimovich; Nematov Abror Akbar ugli (Research Parks Publishers, 2021)
In this article, analysis of mathematical model of designs of the cutting tool of assembled mill with inserted knives with diffusion fastening of hard-alloy plates is given.